BUERGER’S DISEASE - A GENERAL OVERVIEW WITH A FOCUS ON NEW THERAPEUTIC APPROACHES - Kwolek, Marlena; Judzińska, Alicja; Piech, Bartosz; Sobczyńska, Kamila; Ignarska, Justyna; Terbosh , Magda; Kubicz Mzabi , Sabina; Trojanowska, Emilia; Dubaj, Magdalena; Osipowska, Julia (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Buerger's disease (thromboangiitis obliterans, TAO) is an inflammatory disease affecting small and medium-sized blood vessels, primarily in the extremities. This condition leads to their gradual narrowing and occlusion, resulting in impaired blood flow and tissue ischemia. It most often affects young adults, particularly men. It is strongly associated with tobacco use, which is considered a key risk factor for disease development and progression. Clinical presentation includes limb pain, intermittent claudication, ulceration, and, in advanced cases, tissue necrosis. Although treatment is primarily centered on smoking cessation and symptom relief, recent advances in therapeutic approaches show promising potential.Purpose: The aim of this review is to discuss Buerger's disease in the context of its pathogenesis, diagnosis, and clinical presentation, and to analyze current therapeutic options.Methodology: A narrative literature review was conducted in PubMed to identify studies on thromboangiitis obliterans. The search strategy included the keywords "Buerger’s disease" (accounting for variant - "Buerger disease"), "thromboangiitis obliterans" and "treatment". Additionally, reference lists of selected articles were screened to identify further relevant publications. Studies published between 2000 and 2025 and directly related to the topic were included.Conclusions: Advances in the understanding and management of Buerger’s disease have led to the development of new therapeutic approaches. However, current evidence remains limited, and further well-designed studies are needed to establish optimal treatment strategies and improve patient outcomes.